Human capital and social capital in entrepreneurs and managers of small and medium enterprises - Felício, J. Augusto; Couto, Eduardo; Caiado, Jorge (Journal of Business Economics and Management, 2012)
This paper uses factor analysis methods to identify structures associated with human and social capital in a small country with an open-economy, based on a survey of small- and medium-sized companies across different sectors. The purpose of this research is to investigate the influences of entrepreneurial and managerial behaviours on the relationship between human capital and social capital. The results indicate that the principal factor is highly correlated to the variables of experience, professional proficiency and cognitive ability, which are predominant characteristics of the entrepreneur, as well as status variables such as interlinking, family support, personal relations and social relations. The study also suggests that links between human capital and social capital are more salient in manufacturing and construction companies than in the wholesale trade, retail trade and services sectors.